The end of Oz - Paige, Danielle (Novelist) (Paige, Danielle (Novelist). Dorothy must die series, 2017)
Dorothy Gale was buried when the Emerald Palace crashed to the ground; Ozma has been restored to the throne. But girls from Kansas are harder to kill than you'd think. Now Amy Gumm is following the Road of Yellow Brick toward the mysterious land of Ev, where the Nome King rules a bleak and angry world. Surprise! He has a gingham-clad bride. And the line between Good and Wicked is blurring.--